Validation of Artificial Intelligence Expectations and Training Attitudes (AI-ETA) Scale for Pre-service Chemistry Teachers - Dea Santika Rahayu; Rustam Effendy Simamora (Universitas Sulawesi Barat, 2025)
Artificial intelligence (AI) is increasingly integrated into education, requiring valid instruments to assess teachers’ expectations and training attitudes toward its use. This study aims to validate the Artificial Intelligence Expectations and Training Attitudes (AI-ETA) scale for pre-service chemistry teachers. A quantitative survey design was employed, involving 95 participants from two public universities. The instrument consisted of two dimensions: expectations about AI’s impact on education and expectations about AI training courses, measured using a five-point rating scale. Data were analyzed using the Rasch measurement model to examine item fit, reliability, separation, and unidimensionality. The results indicate that the instrument demonstrates strong psychometric properties, with high person reliability and adequate item separation. Most items showed acceptable fit statistics, although a few items required minor refinement. The unidimensionality analysis confirmed that the scale measures a single dominant construct. These findings suggest that the AI-ETA scale is a valid and reliable instrument for assessing pre-service teachers’ perceptions of AI. The study highlights the importance of understanding teachers’ expectations to support effective AI integration in chemistry education.